The effect of carbohydrate and caffeine mouth rinsing on kicking performance in competitive Taekwondo athletes during Ramadan - Pak, I. E.; Cug, M.; Volpe, S. L.; Beaven, C. M. (Journal of Sports Sciences, 2020)
Mouth rinsing has been proposed as a strategy to minimize performance decrements during Ramadan. We investigated the effect of 4 weeks of Ramadan on kicking performance in 27 Taekwondo athletes performing weekly Taekwondo Anaerobic Intermittent Kick Tests (TAIKT). The effects of a placebo, 6.4% glucose and 6-mg/kg caffeine mouth rinses on TAIKT performance and perceived exertion were investigated before, during weekly training sessions, and after Ramadan in a counterbalanced, crossover design. Ramadan had a significant negative impact on the percentage of successful kicks in Week 1 of Ramadan (pre: 76.7±0.4%, Week 1: 69.9±3.2%). The percentage of successful kicks was significantly greater in the caffeine mouth rinse condition compared to the glucose and placebo conditions during the first 3 weeks of Ramadan (caffeine: 38.3±6.8%, glucose: 36.4±6.9%, placebo: 36.0±6.5%). Caffeine decreased perceived exertion during Ramadan (0.74-1.15 AU, p>0.05). Our results showed that Ramadan had a significant negative effect on repeated high-intensity kicking efforts that should be considered when training and competing. Additionally, there were significant positive effects of a caffeine mouth rinse in a sport-specific test. These data suggest that athletes can consider mouth rinsing as a strategy to enhance performance when undertaking training or competition during a period of privation.